PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 009 KAMPUNG DALAM PARIT I/II KECAMATAN SUNGAI APIT - ', Ernawati; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Application of Cooperative Learning Model Group Investigation (GI) in the Learning science aimed at translating the abstract more concrete material, so the material can be conveyed and students absarak Sakan understand and enable the understanding will be stored in the memory of students. This research aims to design programs of learning programs with the application of cooperative learning model of Group Investigation (GI) so that it can improve student learning outcomes, especially the subject of the motion of objects. the implementation of cooperative learning model of Group Investigation to improve learning outcomes IPA third grade students of SDN. 009 Kampung Dalam Kacamatan Sungai Apit. This data was obtained from the data class act. With the formulation of the problem